Systematic Extraction, Isolation, and Phytochemical Investigation of Various Parts of Murraya paniculata (L.) Jack - Sharma, Abhishek; Goshain, Omprakash (Journal of Neonatal Surgery, 2025)
Murraya paniculata (L.) Jack is a member of the Rutaceae family, an aromatic evergreen medicinal shrub generally distributed throughout tropical and subtropical Asia, India, China, Thailand Malaysia and Indonesia. Various plant parts have been utilized in the management of inflammation, diabetes mellitus, microbial infections, gastrointestinal disorders, neurological ailments and pain syndromes used for centuries in diverse ethnomedicinal traditions including but limited to ayurveda. siddha and traditional Chinese medicine. This paper reports a systematic and comprehensive exploration of bioactive phytoconstituents in five different plant parts of M. paniculata via extraction, isolation, chromatographic separation and structural elucidation. Conventional maceration, Soxhlet extraction, ultrasound-assisted extraction (UAE), microwave-assisted extraction (MAE), and supercritical fluid extraction (SFE) were used for multiple extract techniques with solvents of varying polarity (petroleum ether, chloroform, ethyl acetate, methanol and water). (TLC), and reverse-phase high-performance liquid chromatography (RP-HPLC) resulted in compounds such as carbazole alkaloids, coumarins, flavonoids, and a triterpenoid. Ultraviolet-visible (UV-Vis) spectroscopy, Fourier transform infrared (FTIR) spectroscopy, proton and carbon nuclear magnetic resonance (1H/13C NMR) spectroscopies, and high-resolution mass spectrometry techniques were used to confirm the structural characterization. Integrated phytochemical-pharmacological profile disclosed on these findings prunes M. paniculata as an encouraged candidate for pharmaceutical drug discovery and nutraceutical development in the genesis of alternatives that validate its traditional uses